Analisis Perkembangan Pinjaman Pada Fitur Digital Loan Produk Digital Banking di PT. Bank Negara Indonesia (Persero) Tbk Cabang Makassar - Tri Wira Cahya Wulandari; Ansar Mulkin Bas; Pra Gemini (STIM-LPI Makassar, 2026)
The development of loans in the Digital Loan feature of digital banking products at PT. Bank Negara Indonesia (Persero) Tbk Makassar Branch serves as the main basis for writing this thesis. The data taken is from the entire population from 2019 to 2023. As a sample data, this research uses a descriptive quantitative approach. The data source consists of secondary data, which was then analyzed using trend analysis. The results show that the standards set by Bank Indonesia indicate that the average value of online or digital loans in the Digital Loan feature of PT. Bank BNI Makassar Branch, Makassar City Branch for the period 2019-2023 is rated as healthy, with an average of 21%, indicating a fairly good performance in managing loans within banking aspects.